1978
DOI: 10.1042/bj1700235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pent-4-enoate on cellular redox state, glycolysis and fatty acid oxidation in isolated perfused rat heart

Abstract: The metabolic effects of pent-4-enoate were studied in beating and potassium-arrested perfused rat hearts. The addition of 0.8imM-pent-4-enoate to the fluid used to perfuse a potassium-arrested heart resulted in a 70 % increase in the 02 consumption and a 66 % decrease in the glycolytic flux as measured in terms of the de-tritiation of [3-3H]glucose, although the proportion of the 02 consumption attributable to glucose oxidation decreased from an initial 30 % to 10 %. The pent-4-enoate-induced increase in 02 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…These findings appear rather similar to recent observations concerning 5-HD metabolism which besides its inhibitory effect on the K-ATPmito is a substrate for enzymes of the 13-oxidative pathway (8). Taken together, these evidences suggest that the inhibitory effect of 5-HD on lactate production might be ascribed to a slowed glycolytic rate through the inhibition 6-phosphofructokinase due to an increase of citrate (9) or to the accumulation of its own oxidative metabolites (25). On the other hand, these metabolic effects of 5-HD do not seem to be the consequence of the blockade of K-ATPmito since it has been previously found that diazoxide exerted an inhibitory effect on lactate production (10).…”
Section: Discussionsupporting
confidence: 79%
“…These findings appear rather similar to recent observations concerning 5-HD metabolism which besides its inhibitory effect on the K-ATPmito is a substrate for enzymes of the 13-oxidative pathway (8). Taken together, these evidences suggest that the inhibitory effect of 5-HD on lactate production might be ascribed to a slowed glycolytic rate through the inhibition 6-phosphofructokinase due to an increase of citrate (9) or to the accumulation of its own oxidative metabolites (25). On the other hand, these metabolic effects of 5-HD do not seem to be the consequence of the blockade of K-ATPmito since it has been previously found that diazoxide exerted an inhibitory effect on lactate production (10).…”
Section: Discussionsupporting
confidence: 79%
“…We have previously demonstrated that the metabolism of pent-4-enoate and pentanoate in the isolated perfused rat heart is rapid and leads to an accumulation of tricarboxylic acid-cycle intermediates (Hiltunen, 1978;Hiltunen et al, 1978), accompanied by incorporation of H'4CO3-into these intermediates . Moreover, the rate of CO2 fixation was appreciable even in the absence of odd-carbon fatty acids.…”
mentioning
confidence: 99%
“…In earlier experiments performed in our laboratory, pent-4-enoate caused a considerable increase in the concentration of tricarboxylic acid-cycle intermediates in perfused hearts, especially in that of malate, and pentanoate caused a similar metabolic change. These results suggested that acryloyl-CoA formed during the fl-oxidation of pent-4-enoate could undergo reduction in cardiac muscle, after which the C3 compound is metabolized to tricarboxylic acid-cycle intermediates (Hiltunen, 1978;Hiltunen et al, 1978). The enzyme system which reduces acryloyl-CoA in mammalian tissue is not known, and the possibility that pent-4-enoyl-CoA is reduced to pentanoyl-CoA cannot be excluded.…”
Section: Resultsmentioning
confidence: 98%
“…The metabolic fate of the acryloyl group is still uncertain. Perfused liver is able to oxidize pent-4-enoate continuously provided that its concentration in the perfusion medium is not too high (Williamson et al, , 1970), and we have suggested previously, on the basis of experiments say whether the compound reduced is with pent-4-enoate and perfused rat hearts, that cardiac muscle is able to metabolize it by a mechanism in which the carbon skeleton of the acryloyl part of pent-4-enoate is transformed to tricarboxylic acid-cycle intermediates via the propionate pathway (Hiltunen, 1978;Hiltunen et al, 1978). The aim of the present work was to ascertain whether isolated heart mitochondria can metabolize pent-4-enoate.…”
mentioning
confidence: 92%
See 1 more Smart Citation